Utilización de la cromatografía de capa fina para la determinación de compuestos carbámicos en muestras biológicas (contenido gástrico), de cadáveres que ingresan al laboratorio de química forense del departamento de criminalística de chimborazo, durante el periodo de octubre a diciembre del 2010 - Ortiz, Karina (2012)
In the laboratory facilities of Forensic Chemistry of the Department of Chimborazo's Criminology this work has realized as an instrument of benefit towards the collectivity, to the service of the legal Doctor and of the Toxicological Analyst, where there is compiled primary and secondary information of an exhaustive and experimental investigation that I help to announce the different procedures that are realized for the Utilization of the chromatography of thin cap for the determination of compounds carbámicos in biological samples (gastric content), of corpses, for of this form to be able to contribute in the evaluaciones of results. In addition to realize an analysis of the statistical records of samples analyzed by the Department of Criminology of Chimborazo's Province during the period from October to December, 2010 ", where there were analyzed samples of gastric content, for pesticides, in which there is demonstrated that in the majority of corpses the consumption of alcohol and other toxins put in danger the physical, mental, familiar health, and even the death. Also we look that it is a support for the community